1998
DOI: 10.1002/(sici)1099-1379(1998)19:1+<697::aid-job974>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Fitting square pegs into round holes: mapping the domain of contingent work arrangements onto the psychological contract

Abstract: In this paper, we have endeavored to integrate the literature on psychological contracts with the literature on contingent work arrangements. We have further developed the theoretical foundation of the psychological contract and its dimensions. After reviewing previous work on contingent employment, we illustrate how the dimensions of psychological contracts (stability, scope, tangibility, focus, time frame, particularism, multiple agency and volition) highlight the dierences and similarities among alternative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
295
1
9

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 363 publications
(313 citation statements)
references
References 75 publications
8
295
1
9
Order By: Relevance
“…In the case of contingent employment, one might suppose that the expectations of these employees, comparing to direct-hire permanent employees, are initially different. Psychological contracts of contingent workers tend to have more transactional entitlements, involving a specific, short-term period relationship and focusing upon monetary exchange (McLean Parks, Kidder & Gallagher, 1998;De Cuyper & De Witte, 2007). Accordingly, job insecurity may not breach these specific psychological contracts (De Cuyper & De Witte, 2007), since these do not guarantee job security as a basic promise (De Cuyper & De Witte, 2006;Sverke, Gallagher, & Hellgren, 2000).…”
Section: Job Insecuritysupporting
confidence: 70%
See 1 more Smart Citation
“…In the case of contingent employment, one might suppose that the expectations of these employees, comparing to direct-hire permanent employees, are initially different. Psychological contracts of contingent workers tend to have more transactional entitlements, involving a specific, short-term period relationship and focusing upon monetary exchange (McLean Parks, Kidder & Gallagher, 1998;De Cuyper & De Witte, 2007). Accordingly, job insecurity may not breach these specific psychological contracts (De Cuyper & De Witte, 2007), since these do not guarantee job security as a basic promise (De Cuyper & De Witte, 2006;Sverke, Gallagher, & Hellgren, 2000).…”
Section: Job Insecuritysupporting
confidence: 70%
“…One might ascertain that contingent workers establish a contract with their agency, so they develop the idea that this organization has a set of obligations towards them and they are constantly assessing if it is fulfilling them or not. Simultaneously, since these workers stay for a certain period of time at the premises of a client organization they also develop the idea that it also has obligations towards them, which can or cannot be fulfilled (McLean Parks, Kidder & Gallagher, 1998;Druker & Stanworth, 2004;Claes, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Psychological contract theory is the idiosyncratic set of reciprocal expectations held by employees concerning their obligations and their entitlements (McLean Parks, Kidder & Gallagher, 1998). For example, the employee will work for an employer with the expectation that they will receive something in return.…”
Section: Psychological Contract Theorymentioning
confidence: 99%
“…Temporary employees are believed to have explicitly defined transactional contracts rather than relational psychological contracts with their organizations (Connelly & Gallagher, 2004;Guest, 2004a;Guest, 2004b;CoyleShapiro & Kessler, 2000;McDonald & Makin, 2000;Rousseau, 1995;Rousseau & Wade-Benzoni, 1995). Organizational researchers have also suggested that temporary employees' psychological contracts have short and finite time frames, are narrower in scope, and are less dynamic than relationship contracts (Chambel & Alcover, 2011;Connelly & Gallagher, 2004;Coyle-Shapiro & Kessler, 2000;McDonald & Makin, 2000;McLean Parks et al, 1998). Chambel and Castanheira (2006) found that temporary employees hired directly by the organization develop similar psychological contracts as permanent employees, and these temporary employees build up relational psychological contracts with the organization.…”
Section: Psychological Contract Breach Of Contract and Temporary Emmentioning
confidence: 99%